Adherence to guidelines is associated with improved survival following in-hospital cardiac arrest. (October 2020) - Hessulf, Fredrik; Herlitz, Johan; Rawshani, Araz; Aune, Solveig; Israelsson, Johan; Södersved–Källestedt, Marie-Louise; Nordberg, Per; Lundgren, Peter; Engdahl, Johan
Abstract: Background: Most resuscitation guidelines have recommendations regarding maximum delay times from collapse to calling for the rescue team and initiation of treatment following cardiac arrest. The aim of the study was to investigate the association between adherence to guidelines for cardiopulmonary resuscitation (CPR) after in-hospital cardiac arrest (IHCA) and survival with a focus on delay to treatment. Methods: We used the Swedish Registry for CPR to study 3212 patients with a shockable rhythm and 9113 patients with non-shockable rhythm from January 1, 2008 to December 31, 2017. Adult patients older than or equal to 18 years with a witnessed IHCA where resuscitation was initiated were included. We assessed trends in adherence to guidelines and their associations with 30-day survival and neurological function. Adherence to guidelines was defined as follows: time from collapse to calling for the rescue team and CPR within 1 min for non-shockable rhythms. For shockable rhythms, adherence was defined as the time from collapse to calling for the rescue team and CPR within 1 min and defibrillation within 3 min. Results: In patients with a shockable rhythm, the 30-day survival for those treated according to guidelines was 66.1%, as compared to 46.5% among those not treated according to guidelines on one or more parameters, adjusted odds ratio 1.84 (95% CI 1.52–2.22). Among patients with a non-shockable rhythm the 30-day survival for those treated according to guidelines was 22.8%, as compared to 16.0% among those not treated according to guidelines on one or more parameters, adjusted odds ratio 1.43 (95% CI 1.24–1.65). Neurological function (cerebral performance category 1–2) among survivors was better among patients treated in accordance with guidelines for both shockable (95.7% vs 91.1%, <0.001) and non-shockable rhythms (91.0% vs 85.5%, p < 0.008). Adherence to the Swedish guidelines for CPR increased slightly 2008–2017. Conclusions: Adherence to guidelines was associated with increased probability of survival and improved neurological function in patients with a shockable and non-shockable rhythm, respectively. Increased adherence to guidelines could increase cardiac arrest survival.